A TRIZ Based Methodology for the Analysis of the Coupling Problems in Complex Engineering Design - Fei, G.; Gao, James X.; Tang, X. Q. (Cranfield University Press, 2009)
Conceptual design is a critical and innovative stage in engineering product and system design. In the conceptual design process, it would be ideal if all functional requirements are maintained independently according to the law of Axiomatic Design theory. However, in practice, especially in complex engineering product and system design, more often the requirements are not independent (or coupled), and this makes conceptual design more difficult. In this paper, a coupling analysis methodology, framework and related techniques are proposed which integrate axiomatic design with the theory of inventive problem solving (TRIZ), in order to identify and analyse the coupling problems existing in conceptual design. An illustrative example is also presented.
Organised by: Cranfield University
Keywords: New product design; Coupling analysis; Axiomatic design; TRIZ